STRATEGI PENGEMBANGAN USAHA BAWANG GORENG LOKAL PADA DESA TONGGING KECAMATAN MEREK KABUPATEN KARO SUMATERA UTARA - Ryan Kevin Fransiskus Silalahi; Muhammad Agung Anggoro; Munawarah (Mount Hope Management International Journal, 2024)
The objectives of this study are as follows: To analyze and understand the supply chain on consumer satisfaction, to analyze and understand the effect of price on consumer satisfaction, to analyze and understand the effect of partnership on consumer satisfaction, to analyze and understand the effect of supply chain, price, partnership on consumer satisfaction. This type of research is quantitative research, with a population of 32 shallot entrepreneurs who were all used as samples. The results of the study showed that the supply chain has a positive and significant effect on consumer satisfaction with a Sig value to influence the supply chain on consumer satisfaction of 0.005 <0.05 and a Tcount value of 2.723> Ttable 2.048. Price has a positive and significant effect on consumer satisfaction with a Sig value to influence price on consumer satisfaction of 0.004 <0.05 and a Tcount value of 2.842> Ttable 2.048. Distribution channels have a positive and significant effect on consumer satisfaction with a Sig value to influence distribution channels on consumer satisfaction of 0.006 <0.05 and a Tcount value of 2.989> Ttable 2.048. Supply chain, price, and distribution channels simultaneously have a positive and significant effect on consumer satisfaction with a Fcount value of 3.293 greater than Ftable 2.90 and a sig value of 0.03 <0.05.